Efficient Compensation of Transmitter and Receiver IQ Imbalance in OFDM Systems. (16th August 2010) - Tandur, Deepaknath; Moonen, Marc
Abstract : Radio frequency impairments such as in-phase/quadrature-phase (IQ) imbalances can result in a severe performance degradation in direct-conversion architecture-based communication systems. In this paper, we consider the case of transmitter and receiver IQ imbalance together with frequency selective channel distortion. The proposed training-based schemes can decouple the compensation of transmitter and receiver IQ imbalance from the compensation of channel distortion in an orthogonal frequency division multiplexing (OFDM) systems. The presence of frequency selective channel fading is a requirement for the estimation of IQ imbalance parameters when both transmitter/receiver IQ imbalance are present. However, the proposed schemes are equally applicable over a frequency flat/frequency selective channel when either transmitter or only receiver IQ imbalance is present. Once the transmitter and receiver IQ imbalance parameters are estimated, a standard channel equalizer can be applied to estimate/compensate for the channel distortion. The proposed schemes result in an overall lower training overhead and a lower computational requirement, compared to the joint compensation of transmitter/receiver IQ imbalance and channel distortion. Simulation results demonstrate that the proposed schemes provide a very efficient compensation with performance close to the ideal case without any IQ imbalance.